2020
DOI: 10.3390/jcm9061744
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Levels of Periodontal Destruction, Behavioral Risk Factors and Systemic Oxidative Stress in Ischemic Stroke Patients: A Cohort Pilot Study

Abstract: Background: Due to the higher frequency of ischemic stroke in men compared to women, we aimed to determine if gender differences exist regarding periodontal status and several plasma biomarkers in patients with a recent large artery atherosclerosis ischemic stroke (IS). Material and methods: Patients with their first IS within less than six weeks who were able to undergo periodontal examinations were evaluated. Demographic data, periodontal status, oxidative stress parameters/plasma antioxidant capacity, and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 117 publications
4
7
0
Order By: Relevance
“…A poor periodontal status of IS patients was recorded by both the 2012 CDC/AAP and the EFP/AAP classification systems, as revealed by the similarly high periodontitis burden: an overall periodontitis frequency of 98.5% and 97.8%, respectively, and a 75.89% and 96.45% frequency of severe cases, respectively. These results show a higher periodontitis burden compared with previous studies reporting a 79.6% [45] and 73.3% [55] periodontitis prevalence in stroke patients. However, it is important to acknowledge that previous reports were based on the 2012 CDC/AAP classification system [45] and the Community Periodontal Index for Treatment Needs (CPITN) criteria [55], respectively.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…A poor periodontal status of IS patients was recorded by both the 2012 CDC/AAP and the EFP/AAP classification systems, as revealed by the similarly high periodontitis burden: an overall periodontitis frequency of 98.5% and 97.8%, respectively, and a 75.89% and 96.45% frequency of severe cases, respectively. These results show a higher periodontitis burden compared with previous studies reporting a 79.6% [45] and 73.3% [55] periodontitis prevalence in stroke patients. However, it is important to acknowledge that previous reports were based on the 2012 CDC/AAP classification system [45] and the Community Periodontal Index for Treatment Needs (CPITN) criteria [55], respectively.…”
Section: Discussionsupporting
confidence: 59%
“…A poor periodontal status of IS patients was recorded by both the 2012 CDC/AAP and the EFP/AAP classification systems, as revealed by the similarly high periodontitis burden: an overall periodontitis frequency of 98.5% and 97.8%, respectively, and a 75.89% and 96.45% frequency of severe cases, respectively. These results show a higher periodontitis burden compared with previous studies reporting a 79.6% [45] and 73.3% [55] perio-…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…A recent study indicated that female showed higher serum levels such as glycemic values, total cholesterol, and LDL levels which were related to periodontal disease. 39 It might be one reason why female showed high risk for periodontal disease.…”
Section: Discussionmentioning
confidence: 99%